Safety and tolerability of calcitonin-gene-related peptide binding monoclonal antibodies for the prevention of episodic migraine – a meta-analysis of randomized controlled trials. (August 2019) - Xu, Da; Chen, Deng; Zhu, Li-na; Tan, Ge; Wang, Hai-jiao; Zhang, Yu; Liu, Ling
Aim: To systematically evaluate the safety and tolerability of calcitonin-gene-related peptide binding monoclonal antibodies from the results of randomized controlled trials. Methods: Online databases were searched on calcitonin-gene-related peptide binding monoclonal antibodies for the prevention of episodic migraine. Overall withdrawal, withdrawal due to adverse events, adverse events, serious adverse events and specific adverse events were extracted from the included studies. A meta-analysis was performed with Revman 5.3.0 software. Results: Ten studies that investigated four drugs (galcanezumab, erenumab, fremanezumab and eptinezumab) with 5817 participants were included in this study. Serious adverse events, overall withdrawals, withdrawal due to adverse events and any adverse events were not significantly associated with monoclonal antibody treatment. Injection site pain and erythema were significantly higher in the calcitonin-gene-related peptide binding monoclonal antibodies treatment group than in the placebo group. The rates of serious adverse events were significantly higher in the galcanezumab 120 mg group. Injection site erythema was associated with galcanezumab 120 mg and 240 mg. Injection site pain and nasopharyngitis were associated with galcanezumab 150 mg and 5 mg, respectively. Overall adverse events were significantly higher with erenumab 70 mg and 140 mg. Treatment-related adverse events were significantly higher with fremanezumab 225 mg/month and 675 mg/quarter. Conclusions: This study provides data on the safety and tolerability profiles of calcitonin-gene-related peptide binding monoclonal antibodies and confirms their potential use as preventive treatments for episodic migraine. In addition to the acceptable withdrawal rates, serious adverse events were rare, and the severity of most adverse events was mild to moderate. Injection site reaction may be the major adverse event associated with galcanezumab.